Antioxidant and Antibacterial Activities of Endophytic Fungi Extracts of Syzygium zeylanicum - Syarifah; Elfita; Hary Widjajanti; Arum Setiawan; Alfia Rahma Kurniawati (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Syzygium zeylanicum, one of the other therapeutic plants found in Indonesia, is used to treat various ailments, such as antimicrobial, anti-inflammatory, antioxidant, arthritis, antidiabetic, mosquitocidal, antitumor, and anti-rheumatic agents. The massive use of plant extracts has caused the development of isolation of bioactive compounds thru their endophytic. The present research aimed to obtain endophytic fungal isolates from the stem bark and leaves of Jambu nasi-nasi (S. zeylanicum) and analyze endophytic fungal extracts’ antioxidant and antibacterial activity. Endophyte identification was performed morphologically, and isolates with high biological activity were molecularly characterized. The antibacterial activity was evaluated by the disc diffusion method, and the antioxidant activity was evaluated by the DPPH method. In total, 10 endophytic fungi were isolated and identified as Phialemonium sp. (Code SZT3), Acremonium sp. (Code SZT4), Trichoderma aureoviridae (Code SZT5), Trichoderma koningi (Code SZT7), Phytium torulosum (Code SZL1), Phytium zingiberum (Code SZL2), Septonema sp. (Code SZL3), Lasiodiplodia pseudotheobromae (Code SZL4), Volutella cilliata (SZL5), and Trichophyton mentagrophytes (Code SZL7). Isolate SZL4 gave activity the highest antioxidant (IC50 = 3.30 ????g/mL) and strong antibacterial activity against four pathogens bacterial (S. thypi, B. subtilis, S. aureus, and E. coli). The potential endophytic fungi based on molecular analysis was Lasiodiplodia pseudotheobromae with accession number OK668257. These endophytic fungi can be developed into new sources of antibacterial and antioxidant bioactive compounds through further studies.